MENINGKATKAN SIKAP PENERIMAAN DIRI PADA LANSIA DI PANTI WERDHA TROPODO MELALUI KEGIATAN KELOMPOK KECIL EVANGELISASI - Lh, gitalh (Pastoralia Jurnal Penelitian Dosen, 2024)
Elderly or elderly is a stage of life that begins at the age of around 60 years and above. Biologically, the elderly population is also a population that experiences a continuous aging process, which is characterized by a decrease in physical endurance, namely increasing susceptibility to disease attacks that can cause death. . This stage is characterized by significant physical, psychological, and social changes. Therefore, an important aspect of a person's well-being, especially in old age, is an attitude of self-acceptance. Self-acceptance refers to the ability to accept and love oneself, including one's strengths, weaknesses and limitations. Self-acceptance is very important for the elderly because it can affect their quality of life, happiness and overall life satisfaction in their old age. The purpose of this writing is to determine whether the implementation of small group Evangelization activities can improve the attitude of self-acceptance for the elderly at the Bhakti Luhur Tropodo Nursing Home, Sidoarjo, East Java. This research uses a qualitative approach with the interview method as the main tool for collecting data.  The number of subjects used was five elderly people at the Bhakti Luhur Tropodo Nursing Home. The research results found that KKE had a positive impact on the self-acceptance process of the elderly. These activities help seniors accept weaknesses and limitations, increase self-confidence, and provide important emotional support. KKE plays an important role in supporting older people to better accept themselves and live in supportive faith communities. KKE not only provides space for spiritual growth, but is also a place where seniors can feel togetherness, support and brotherly love in carrying out the call of faith, thereby improving their overall well-being.